ECONOMIC ANALYSIS OF INTEGRATED PEST MANAGEMENT IN CHERRY CULTIVATION - Gül, Mevlüt; Akpınar, Metin Göksel; Demircan, Vecdi; Acar, Musa (UNIV AGRICULTURAL SCIENCES & VETERINARY MEDICINE BUCHAREST, 2016)
The present study aims to develop new suggestions by determining the implementation level of integrated pest management, awareness level regarding the integrated pest management, shortcomings in implementation and efficiency of implementation in cherry cultivation in the region that stands out in Turkey. In this context, Izmir, Manisa, Konya, Isparta, Afyon and Denizli were taken into the scope of research where intensive cultivation of cherry in Turkey takes place. According to the results of the study integrated pest management awareness is low. However, the integrated pest management methods have been implemented more since cherry started to be exported. 37.3% of farmers highly implement integrated pest management and 22.5% implements at low level. The lack of awareness at enterprise level regarding integrated pest management and warning system is the area need to be focused. At the top of the suggestions about increasing the efficiency of the system comes popularizing the training activities in the region. Overall, providing sustainability of the system, development of production and consumption culture are important areas both in public and private sectors.
Keywords: Cherry production; IPM; Turkey